Three-Channeled Aortic Dissection in a Patient without Marfan Syndrome - Arita, Yoshie Inoue (Ann Thorac Cardiovasc Surg, 2017)
A 64-year-old man was admitted for evaluation of back pain. He did not have a Marfan syndrome (MFS)-like appearance, and had a history of a type B aortic dissection and total arch replacement. A connective tissue disorder had been suspected because of the histologic findings of the resected aortic wall. On admission, a computed tomography (CT) scan demonstrated a three-channeled aortic dissection (3ch-AD) measuring 63 mm in diameter. We planned to perform elective surgery during his hospitalization. On the fourth hospital day, he complained of severe back pain, and enhanced CT scan revealed an aortic rupture. The patients with 3ch-AD often have MFS. However, even if they do not have an MFS-like appearance, clinicians should consider fragility of the aortic wall in patients with 3ch-AD. If the aortic diameter is enlarged, early surgery is recommended. In particular, if a connective tissue disorder is obvious or suspected, emergent surgery is warranted.